Street Children in Aceh: Cultural, Economic, and Institutional Determinants of Vulnerability - Lisa Fitriani; Sanisah Saidi; Suryani Sulistiana Susanti; Dara Febriana (GLOBAL HEALTH SCIENCE GROUP, 2025)
Street children remain a critical social issue in Indonesia, particularly in Aceh Province, where cultural, economic, and institutional factors shape their vulnerability. This study explores the lived experiences of street children in Aceh and identifies the underlying factors that perpetuate their street involvement. A qualitative embedded case study was conducted using semi-structured interviews, non-participant observations, and document analysis. A total of 41 participants were involved, consisting of street children, caregivers, and family members. Data were collected through in-depth semi-structured interviews conducted in shelters, community centers, and street locations to capture diverse lived experiences and perspectives. Non-participant observations were carried out to explore daily routines, interactions, and coping strategies in natural settings. Additionally, relevant institutional and community documents were analyzed to provide contextual understanding and triangulate the data. All interviews were audio-recorded with participants’ consent and transcribed verbatim for thematic analysis. Data were analysed thematically and triangulated across sources. Five interrelated factors emerged: family dysfunction, the culture of giving, poverty, criminal exploitation, and weak institutional support. Street children often transition from unsafe family environments to street life, which provides temporary survival but exposes them to exploitation and trauma. Placement in childcare institution orphanages offers safety but presents challenges of adjustment, lack of family support, and insufficient psychosocial services. Reintegration into society remains fragile due to the absence of structured follow-up support. The phenomenon of street children in Aceh is sustained by cultural, economic, and systemic factors. A holistic intervention is required, integrating family strengthening, culturally sensitive community engagement, and trauma-informed institutional care.